2017
DOI: 10.7863/ultra.16.02052
|View full text |Cite
|
Sign up to set email alerts
|

Size of Sclerosing Foams Prepared by Ultrasound, Mechanical Agitation, and the Handmade Tessari Method for Treatment of Varicose Veins

Abstract: Objectives-Sclerotherapy is a therapeutic method used in the treatment of varicose veins and works by occluding damaged blood vessels with a chemical solution.Foam sclerotherapy is an attractive treatment because the results are more effective than those obtained by using liquid sclerosants. However, serious neurologic complications, which are likely related to air embolism, have been reported after treatment with foams generated by the handmade method (Tessari technique) most often used clinically. We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Depending on surfactant concentration (Bai et al, 2018), liquidto-gas ratio-also referred to as foam quality in the literature (Cameron et al, 2013), method of production (Carugo et al, 2013;Critello et al, 2017), syringe type and needle size , and bubble size distribution-also referred to as size dispersity in the literature (Cameron et al, 2013;Carugo et al, 2016;Critello et al, 2017); the stability of the resulting foam can vary (Cavezzi & Tessari, 2009).…”
Section: Conventional Clinical Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Depending on surfactant concentration (Bai et al, 2018), liquidto-gas ratio-also referred to as foam quality in the literature (Cameron et al, 2013), method of production (Carugo et al, 2013;Critello et al, 2017), syringe type and needle size , and bubble size distribution-also referred to as size dispersity in the literature (Cameron et al, 2013;Carugo et al, 2016;Critello et al, 2017); the stability of the resulting foam can vary (Cavezzi & Tessari, 2009).…”
Section: Conventional Clinical Methodsmentioning
confidence: 99%
“…The gas canister is then replaced with a Varithena® transfer unit which allows the withdrawal of foam into a syringe (Modified and Reprinted from Carugo D. et al, Copyright [2015], distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/)) produce sclerosing foams. It has been reported that foams can also be produced by mechanical agitation of a surfactant solution via acoustic cavitation, using either a tip sonicator (Critello et al, 2017) or under the effect of an ultrasound field in a non-flowing fluid system (Fiorillo, Fiorillo, Critello, & Pullano, 2015). A study demonstrated that low-frequency ultrasound can produce foams with smaller bubbles compared to PCF foams.…”
Section: Alternative Methods Of Foam Productionmentioning
confidence: 99%
See 3 more Smart Citations